The application of Kubler-Ross model in Newly Diagnosed Patients with Relapsing-Remitting Multiple Sclerosis - Giorgia Teresa Maniscalco; Antonio Rosario Ziello; Valentina Panetta; Giovanni Guarcello; Giovanni Improta; Ciro Florio (Archives of Depression and Anxiety - Peertechz Publications, 2019)
Background: Anxiety and depressive disorders affect Multiple Sclerosis (MS) patients since the early stages of the disease. Although the presence of these symptoms is widely recognized, the beginning and the psychological mechanisms at the basis of these disorders have rarely been examined in detail. This observational study aims to assess the presence of emotional distress in the early stages of the disease in patients with relapsing-remitting MS (MS-RR) and to check similarities and dissimilarities with a shared conceptual framework: the "curve of change" of the Kubler-Ross model.